The Road to Culturally Relevant Pedagogy: Expatriate teachers' pedagogical practices in the cultural context of Saudi Arabian higher education - Hamdan Alghamdi, Amani (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
This case study explored the need for culturally relevant pedagogy (CRP) in Saudi Arabian higher education, especially when students have a cultural background that differs from that of their instructor. The study documented how expatriate teachers structured their pedagogical practices in the Saudi Arabian context. It examined how these university teachers attempted to proactively accommodate students’ needs, prior experiences and performance, and how they promoted academic progress while teaching in a different culture. Six themes were revealed: (1) the challenges of constructivism in the Saudi Arabian context; (2) linking pedagogy to the lives of Saudi students; (3) alternating and adjusting teaching to address student needs; (4) connecting with students’; (5) discrepancies in teachers’ beliefs; and (6) teachers’ assumptions and expectations about knowledge. It is argued that CRP offers opportunities for better learning experiences for Saudi students. Through CRP, learning can be made more meaningful and can help in the development of a positive student identity. Some pedagogical strategies are offered to help teachers implement CRP.